Using de-identified linked data to investigate potential to scale a young-parents program: An example from South Australia. - Dobrovic, Jessica; Girolamo, Nadia Di (International Journal of Population Data Science, 2025)
Objectives To use datasets and information available in our state based de-identified linked administrative data platform to investigate the potential for scaling a young parents group aiming to prevent intergenerational contact with the child protection system, to another area of South Australia. Methods The Better Evidence Better Outcomes Linked Data platform (BEBOLD) was used to construct a cohort with eligibility criteria that matched the current participants attending the group at the current service delivery location. Eligibility criteria emulated in the data platform was to be a first-time parent, under the age of 23 at birth of your child, and for the parent to have had contact with the child protection system during their childhood. Two comparison groups with different geographic boundaries were then defined, based on the same eligibility criteria, and a fourth comparison group was constructed referencing the total population of first-time mothers in South Australia. Results Using de-identified datasets in BEBOLD including homelessness, hospital admission and emergency department information, child protection, antenatal characteristics, and birth registrations, we were able to demonstrate in each geographic group, any patterns in system contact that could contribute to an evidence base for scaling a young parents program to that geographic area. We were also able to show the differences in outcomes for young first-time parents compared to all first-time parents across South Australia, to be able to further contextualise experiences of young, first-time parents. Conclusion Through leveraging available information in the BEBOLD platform. We were able to build evidence for a scaling location for a program to support young, first-time mothers with a history of contact with the Child Protection system to another area of South Australia and build an understanding of service contact patterns for first-time parents.